Evaluasi Tingkat Kepuasan Mahasiswa Universitas Almuslim Terhadap Kualitas Pelayanan Pendidikan Tinggi dengan Model HEdPERF - Rahmawati, Rahmawati; Permana, Johar; Rahyasih, Yayah; Triatna, Cepi; Wahyuni, Sri (Universitas Negeri Malang, 2024)
Abstract: This study evaluates student satisfaction at Universitas Almuslim concerning the quality of higher education services using the Higher Education Performance (HEdPERF) model. The research aims to assess the impact of six HEdPERF dimensions, which are non-academic, academic, university reputation, access, program issues, and understanding, on student satisfaction levels. Employing a non-experimental, correlational approach, the study gathered cross-sectional data from 572 students using a structured questionnaire. Validity and reliability of the instrument were tested via Pearson’s correlation and Cronbach’s Alpha. Data analysis was conducted with non-parametric tests, including Chi-Square and Spearman’s correlation, to establish the relationships between perceived service quality and satisfaction. Results indicate a significant positive correlation between all six HEdPERF dimensions and student satisfaction, with stronger associations for dimensions such as university reputation, access, and program issues. The findings suggest that service quality directly influences student satisfaction, supporting HEdPERF as a suitable model for evaluating educational services in higher education. Consequently, enhancing these dimensions could bolster student satisfaction and improve institutional competitiveness. This study highlights the importance of tailored service strategies that address both academic and non-academic aspects, contributing to the broader discourse on quality assurance in higher education. Keywords: Student Satisfaction; higher education services, HEdPERF model, service quality. Abstrak: Penelitian ini mengevaluasi kepuasan mahasiswa di Universitas Almuslim terkait kualitas layanan pendidikan tinggi dengan menggunakan model Higher Education Performance (HEdPERF). Penelitian ini bertujuan untuk menilai dampak enam dimensi HEdPERF, yaitu non-akademik, akademik, reputasi universitas, akses, isu program, dan pemahaman, terhadap tingkat kepuasan mahasiswa. Dengan menggunakan pendekatan korelasional non-eksperimental, penelitian ini mengumpulkan data cross-sectional dari 572 mahasiswa menggunakan kuesioner terstruktur. Validitas dan reliabilitas instrumen diuji melalui korelasi Pearson dan Cronbach’s Alpha. Analisis data dilakukan dengan uji non-parametrik, termasuk Chi-Square dan korelasi Spearman, untuk menetapkan hubungan antara kualitas layanan yang dirasakan dan kepuasan. Hasil penelitian menunjukkan korelasi positif yang signifikan antara keenam dimensi HEdPERF dan kepuasan mahasiswa, dengan asosiasi yang lebih kuat untuk dimensi seperti reputasi universitas, akses, dan isu program. Temuan penelitian menunjukkan bahwa kualitas layanan secara langsung memengaruhi kepuasan mahasiswa, mendukung HEdPERF sebagai model yang sesuai untuk mengevaluasi layanan pendidikan di pendidikan tinggi. Oleh karena itu, peningkatan dimensi-dimensi ini dapat meningkatkan kepuasan mahasiswa dan meningkatkan daya saing institusi. Studi ini menyoroti pentingnya